Antipathogenic properties and applications of low-dimensional materials - Z. L. Shaw (Nature Portfolio, 2021)
Antimicrobial resistance is a growing global problem and low dimensional materials have emerged as a potential solution. Here, the authors review the progress which has been made on low dimensional antimicrobials looking at the materials synthesis, modes of action and currently applications.